Estimation of Equilibrium-Adsorption Behavior at Cryogenic Temperatures of CO2 and N2 Using a Simple Predictive Tool - Bahadori, Alireza (Society of Pertroleum Engineers, Inc, 2011)
Conventionally, carbon dioxide (CO2) removal requires the use of a water-based amine solution and large absorber and regeneration towers. The capital and ongoing operational costs for this process are substantial, and the use (regeneration and disposal) of the amine solution can be problematic from the perspectives of both safety and the environment. Nitrogen (N2) can also be a problematic impurity in natural gas. Many researchers have been investigating the use of alternative gas-separation technologies (such as membranes and adsorption) targeted at removing N2 or CO2 from natural gas more efficiently. In this work, a simple-to-use predictive tool that is easier than existing approaches, is less complicated, and requires shorter computational times is applied to accurately predict the CO2 and N2-adsorption isotherms at low temperatures and pressures up to saturation for a commercial carbon molecular sieve as a function of temperature and partial pressure of these components. Accurate prediction of such data is useful in evaluating the feasibility of using pressure-swing adsorption to separate N2 and CO2 from natural gases at cryogenic temperatures. The proposed method showed consistently accurate results across the investigated wide pressure and temperature ranges, with an average absolute deviation of less than 1% for both N2 and CO2 compared to the existing Toth equation, which shows deviations of 3.5 and 1% for N2 and CO2, respectively. This simple-to-use approach can be of immense practical value for engineers and scientists to have a quick check on adsorption capacities of a given adsorbent at various temperatures and pressures without the necessity of any experimental measurements. In particular, natural-gas-process engineers would find the proposed approach to be user friendly, involving transparent calculations with no complex expressions.